KOMPOSISI PROKSIMAT, SIFAT SENSORI, DAN PENDUGAAN MASA SIMPAN SAMBAL IKAN BETE-BETE - Asnani Asnani; Indriani Indriani; Amir Husni; Nurfitri Ekantari; Suadi Suadi; Ima Wijayanti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2022)
Sambal is a side dish, one of the variants of which is basic chili sauce with additional ingredients of various types of fish such as bete-bete fish (Leiognathus sp). The purpose of this study was to examine the proximate composition and sensory properties (hedonic and description) and to determine the shelf life of bete-bete fish sauce (SIB) using the Accelerated Shelf Life Testing (ASLT) method using the parameters of the total content of bacteria and molds in the chili sauce. The treatments included the use of fish (%) and basic chili sauce (%) with a ratio of 50:50 (SIB1), 40:60 (SIB2), and 30:70 (SIB3). The results showed that the highest proximate composition of SIB was protein and fat with a range of 35.23+1.56 - 42.32±0.45% and 21.14±0.13 - 32.53±1.75, respectively. %. The most desirable sambal (sensory hedonic test) is SIB3, which has the characteristics of appearance: red color typical of fish sauce, slightly bright, brilliant, homogeneous, clean and attractive, aroma: typical of fish sauce is strong, fragrant and fresh, and the consistency is not thick with taste. which is delicious, typical of fish sauce, spicy and somewhat savory. Based on the total parameters of bacteria and molds, it is suspected that the bete-bete fish sauce (SIB3) has a shelf life of 22, 19 and 18 days, respectively, at storage temperatures of 20, 25 and 27 °C.